2010
DOI: 10.2478/v10019-010-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in combination with vascular-targeted therapies

Abstract: BackgroundGiven the critical role of tumor vasculature in tumor development, considerable efforts have been spent on developing therapeutic strategies targeting the tumor vascular network. A variety of agents have been developed, with two general approaches being pursued. Antiangiogenic agents (AAs) aim to interfere with the process of angiogenesis, preventing new tumor blood vessel formation. Vascular-disrupting agents (VDAs) target existing tumor vessels causing tumor ischemia and necrosis. Despite their gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 74 publications
1
18
0
1
Order By: Relevance
“…Several preclinical and clinical trials have proved the safety and efficacy of apatinib as a part of anti-angiogenic treatment (16,17); it was shown that apatinib can "normalize" tumor blood vessels and reduce vascular permeability. Furthermore, apatinib may increase oxygenation by normalization of tumor vasculature and regulation of the tumor microenvironment, thus increasing overall radiosensitivity (18). Taken together, these were some factors leading to the use of apatinib in this patient, along with ease of administration and lower costs as compared with intravenous bevacizumab.…”
Section: Discussionmentioning
confidence: 87%
“…Several preclinical and clinical trials have proved the safety and efficacy of apatinib as a part of anti-angiogenic treatment (16,17); it was shown that apatinib can "normalize" tumor blood vessels and reduce vascular permeability. Furthermore, apatinib may increase oxygenation by normalization of tumor vasculature and regulation of the tumor microenvironment, thus increasing overall radiosensitivity (18). Taken together, these were some factors leading to the use of apatinib in this patient, along with ease of administration and lower costs as compared with intravenous bevacizumab.…”
Section: Discussionmentioning
confidence: 87%
“…Antiangiogenic treatment normalizes tumour vasculature and oxygenation 24 . A combination of rt and mctx can lead to better clinical efficacy in various cancers, because antiangiogenic therapy increases oxygenation and radiosensitivity 23,25 , augmenting radiation efficacy 26 . Our findings might confirm a study reported by Sterba et al 15 , who showed encouraging results for rt combined with metronomic temozolomide in children with medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Учитывая ключевую роль гипоксии в радиоустойчивости, ингибиторы ангиогенеза, такие как ингибиторы VEGF, могут представлять интерес для разрушения этого порочного круга между ангиогенезом и радиорезистентностью путем нормализации сосудистой сети опухоли. Эта нормализация снижает гипоксию и улучшает радиочувствительность раковых клеток и эндотелиальных клеток [35][36][37]. Также не отмечено увеличения токсичности или кровоизлияния в мозг при совместном применении бевацизумаба с облучением всего головного мозга с использованием стандартного фракционирования лучевой терапии.…”
Section: антиангиогенная терапия пациентов с симптоматическими метастunclassified